Iran’s Engagement in Syrian Conflic t. Causes and Consequences - OŻAROWSKI, Rafał (Przegląd Strategiczny, 2018)
Since the 2011, Iran is deeply engaged in Syrian war in order to support and keep President Bashar al-Assad in power. Firstly, Iran started with political and diplomatic support and later turned into military and economic assistance. At the moment, it is believed that Syria is financially sustained by Iran. The main reason that Iran has determined for wide-scale engagement was the existential need for maintaining and then expanding its own regional power influences in the Middle East. If Syrian regime collapsed, Iran would be dealt with a big dilemma and it would loss Syria as a key military and political ally. Thus, Iran would have cut off his transit route to supply weapons to Lebanon for Hezbollah, as these transports still go across Syrian territory. It would surely diminish the Iranian position in the Middle East. Preventing such a case, Iran has been determined to engage in the Syrian conflict to a great extent, which, as a consequence, is charged with heavy costs. Although there is no exact data of Iran’s expenses for the Syrian War, it is supposed that this is in the range of 6 billion USD to 35 billion USD. At the moment, it can be said that engagement in Syrian war was beneficial for Iran, mainly in political sphere, yet the full consequences of this involvement will only be known in many months.